2014
DOI: 10.3748/wjg.v20.i29.10144
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence and management of cancer of the ampulla of Vater

Abstract: Cancer of the ampulla of Vater is still uncommon, but its incidence increased for men in Burgundy. Diagnosis is often made at an advanced stage, dramatically worsening the prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 28 publications
3
51
1
3
Order By: Relevance
“…The present study assessed the clinicopathologic characteristics and survival rates according to stage of both eastern and western patients with AoV cancer. Although previous studies have reported 5‐year OS rates of 40–60%, those studies reported findings from single institution or countries . In contrast, we collected data from two institutions, SNUH in Korea and JHMI in the USA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study assessed the clinicopathologic characteristics and survival rates according to stage of both eastern and western patients with AoV cancer. Although previous studies have reported 5‐year OS rates of 40–60%, those studies reported findings from single institution or countries . In contrast, we collected data from two institutions, SNUH in Korea and JHMI in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…However, previously reported prognosis of patients with AoV cancer was relatively poor and heterogeneous, raising questions about the accuracy of data, especially information in the Surveillance, Epidemiology and End Results (SEER) database . Moreover, there is limited information about stage distribution and prognosis based on ethnicity and geography .…”
Section: Introductionmentioning
confidence: 99%
“…4 As a result, AAC is more likely to be resectable at the time of diagnosis and resection rates of AAC are reportedly higher as compared to other periampullary cancers (50% vs 10%). 5,6 In addition, patients with ampullary cancer tend to have a better prognosis with 5-year survival rates of 30 -70% after resection. 1,[6][7][8][9][10] This broad range of survival could be explained by the morphological heterogeneity in AAC, which complicates the prediction of individual prognosis and clinical decision making with regard to adjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In addition, patients with ampullary cancer tend to have a better prognosis with 5-year survival rates of 30 -70% after resection. 1,[6][7][8][9][10] This broad range of survival could be explained by the morphological heterogeneity in AAC, which complicates the prediction of individual prognosis and clinical decision making with regard to adjuvant therapy. Because of the anatomical confluence of three structures (duodenum, pancreatic and common bile duct), different histopathologic subtypes have been identified in AAC, based on the epithelium of their origin; intestinal, pancreaticobiliary or a mixed type.…”
Section: Introductionmentioning
confidence: 99%
“…PDAC is the fourth most common cause of cancer death in Europe (Ferlay et al , 2010; Rostain et al , 2014; Ryan et al , 2014; Malvezzi et al , 2016; Siegel et al , 2016). …”
mentioning
confidence: 99%